2013
DOI: 10.1038/nature12586
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming in vivo produces teratomas and iPS cells with totipotency features

Abstract: Reprogramming of adult cells to generate induced pluripotent stem cells (iPS cells) has opened new therapeutic opportunities; however, little is known about the possibility of in vivo reprogramming within tissues. Here we show that transitory induction of the four factors Oct4, Sox2, Klf4 and c-Myc in mice results in teratomas emerging from multiple organs, implying that full reprogramming can occur in vivo. Analyses of the stomach, intestine, pancreas and kidney reveal groups of dedifferentiated cells that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
464
7
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(504 citation statements)
references
References 43 publications
11
464
7
4
Order By: Relevance
“…Although targeting the stem cell microenvironment is believed to be important for proper tissue reprogramming (reviewed in ref. 58), earlier attempts at induced in vivo reprogramming in rodent models have resulted in the appearance of teratomas in multiple tissues (59). Our observation may be linked to the extraordinary plasticity of fish gonads compared with most other vertebrate tissues (60,61), and constitutes an aspect that deserves further study.…”
Section: Discussionmentioning
confidence: 91%
“…Although targeting the stem cell microenvironment is believed to be important for proper tissue reprogramming (reviewed in ref. 58), earlier attempts at induced in vivo reprogramming in rodent models have resulted in the appearance of teratomas in multiple tissues (59). Our observation may be linked to the extraordinary plasticity of fish gonads compared with most other vertebrate tissues (60,61), and constitutes an aspect that deserves further study.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, it was observed that the in vivo induction of OSKM in adult mice generated iPS cells that could differentiate towards embryonic and extraembryonic lineages both in vitro and in vivo [37]. These iPS cells have a transcriptional profile that correlates more strongly with ES cells than iPS cells generated by standard in vitro induction of the four transcription factors.…”
Section: Totipotent Cellsmentioning
confidence: 99%
“…Recently, Abad et al 12 achieved this difficult task. In this striking study, the authors generated reprogrammable mice carrying a doxycycline-inducible cassette encoding the four reprogramming factors and demonstrated that the reprogrammed iPSCs acquired totipotent characteristics that were passed on by the zygote and its immediate daughter cells, which in vitro-generated ESCs and iPSCs could not accomplish.…”
Section: Advances In Ipsc Generation Methodsmentioning
confidence: 99%